The use of off-label medications in substance abuse treatment programs. Issue 3 (2nd July 2020) - Paino, Maria; Aletraris, Lydia; Roman, Paul M.
Abstract: Background: Substance use disorder (SUD) treatment centers serve a population of clients who have diverse needs, and may desire or require access to varied treatments while seeking care for their SUDs. While pharmacotherapies have increased in popularity for the treatment of SUDs, adoption rates do remain quite low. But a wider array of pharmacotherapies has become available in recent years which may shift the trend. This article helps shed light on how variations in SUD treatment centers develop and persist with regard to the adoption and delivery of off-label medications. Methods: We use a nationally representative and longitudinal sample of SUD treatment centers in the US ( N = 196). We use a logistic regression to analyze the relationship between organizational characteristics and offering any medications, off-label. We also use a negative binomial regression to analyze the relationship between organizational characteristics and the number of medications that were used off-label. Results: Our findings reveal that older centers, accredited centers, and centers that offer mental health screenings are all positively associated with the provision of off-label medication in SUD treatment. We also find a positive relationship between private funding and offering a greater number of off-label medications. Conclusions: Our results suggest that SUD clients who seek treatment from centers that offer medications off-label, may have access to a greater number of medication-assisted treatment options.